Enhancing the Microstructure and Mechanical Properties of Lost Foam Cast A356 Alloy via Orbital Shaking - Kilic, Oznur; Acar, Serhat; Guler, Kerem Altug (SPRINGER INT PUBL AG, 2026)
The mechanical performance of cast aluminum alloys is closely associated with their solidification microstructure, where a fine and homogeneous dendritic structure plays a critical role in achieving high strength and ductility. In this study, orbital shaking is investigated as a dynamic solidification control technique for refining the microstructure of A356 aluminum alloy produced by the lost foam casting (LFC) process. Casting experiments were carried out using expanded polystyrene (EPS) patterns at pouring temperatures of 720 degrees C and 780 degrees C. Orbital shaking speeds were varied between 50 and 200 rpm, and static castings were used as reference conditions. Microstructural characterization focused on the evaluation of secondary dendrite arm spacing (SDAS) and eutectic silicon morphology. The results show that low-to-moderate shaking intensities lead to a significant refinement in SDAS and improve material density by enhancing interdendritic feeding. At a pouring temperature of 720 degrees C, a shaking speed of 50 rpm reduced the SDAS from 91 to 65 & micro;m, resulting in a marked increase in tensile strength from 141.4 to 172.4 MPa. In contrast, excessive shaking at 200 rpm caused microstructural coarsening and increased porosity, which are likely associated with intensified melt convection and altered feeding behavior in the semisolid state. Importantly, no visible coating damage or detachment was observed under the applied shaking conditions, indicating that orbital shaking does not induce mold-related defects such as penetration or cracking, which are commonly encountered in conventional mechanical vibration processes.
Keywords: lost foam casting; A356 aluminum alloy; orbital shaking; dendritic refinement; microstructure; VIBRATION FREQUENCY; FRACTURE-BEHAVIOR; IRON; Metallurgy & Metallurgical Engineering